Representasi Daerah Istimewa Yogyakarta dalam Film Merindu di Jogja pada Konten YouTube @PaniaradyaKaistemewaan - Sholihah, Wirda Amalia; Fernando, Joshua; Supiyandi, Andi; Lukitowati, Suci (Universitas Muhammadiyah Prof. DR. Hamka, 2025)
Daerah Istimewa Yogyakarta (DIY) has become a popular tourist destination in Indonesia, and this popularity is further enhanced by films as a promotional medium. The short film Merindu di Jogja, uploaded to the YouTube channel @PaniaradyaKaistimewaan on June 8, 2024, is one such example that centers its narrative on Yogyakarta. Based on this phenomenon, this study aims to explore the representation of DIY in the film Merindu di Jogja using a qualitative method with text analysis. The author selected six scenes for examination through John Fiske’s semiotic analysis, which is divided into three levels: the level of reality, the level of representation, and the level of ideology. The findings of this study show that Merindu di Jogja primarily introduces DIY. At the level of reality, DIY is visually represented through codes of appearance, behavior, and environment to illustrate the customs, culture, geography, history, and philosophical axis of Yogyakarta. The level of representation is conveyed through technical codes such as lighting, cinematography, music, and sound to strengthen the impressions or realities depicted in the film, helping viewers to grasp the meaning of each scene. Meanwhile, at the level of ideology, the actions and behavior of the main character, Regita, seek to portray DIY as a nationalist region that embodies Pancasila ideology in daily life. Furthermore, the semiotic elements representing DIY suggest that this film serves as a tool to promote DIY as an attractive, authentic tourist destination capable of offering memorable experiences.